PELATIHAN PEMBUATAN BROSUR BISNIS DAN FLYER PEMASARAN MENGGUNAKAN MICROSOFT WORD PADA SMK BUDI AGUNG - Syahputri, Nita; Indriani , Ulfah; Syahputra, Andrian; Faris, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2022)
The purpose of community service activities is to implement the Tri Dharma of Higher Education and provide learning how to make business brochures and marketing flyers using Microsoft Word at Budi Agung Vocational School. Brochures and flyers are two of several methods that can be used in the marketing process. Both are designed and printed on paper and generally distributed to the general public as promotional media for certain products, services or campaigns. In marketing, good promotional media is needed in order to attract public interest. There are still many who think that Microsoft Word can only be used to type documents. In fact, the latest Microsoft Word update can be used for other things as well, one of which is to design business brochures and marketing flyers. Through training for Budi Agung Vocational High School students, it is hoped that they will be able to use Microsoft Word to make brochures and flyers as promotional and marketing media tools